A systems approach to sustainable finance: Actors, influence mechanisms, and potentially virtuous cycles of sustainability - Beatrice Crona; Garry Peterson; Megan Meacham; Giorgio Parlato; Steven J. Lade; Juan C. Rocha; Victor Galaz (iScience, 2025)
Summary: Over the past decade, corporate investors have increasingly recognized that responsible environmental and social practices are essential to long-term financial success. Despite growing interest, corporate practices remain largely unchanged, and planetary trends are deeply concerning. This review applies a systems analysis lens to understand how financial sector structures and actors influence sustainability outcomes, often in counterproductive ways. Key barriers include the lack of science-based metrics, poor integration of environmental risks, and limited capacity to evaluate complex system dynamics. Current financial practices frequently miss or misinterpret systemic sustainability risks. We identify three critical areas where collaboration between sustainability science and finance is urgently needed: (1) translating scientific insights into financial decision contexts, (2) supporting science-based corporate sustainability reporting, and (3) strengthening environmental impact assessment. Systems thinking helps clarify where financial leverage can drive meaningful, cross-scale change—an essential step toward aligning capital flows with long-term ecological resilience and sustainability goals.